Integration as unrealised ideal of ERP systems: An exploration of complexity resulting from multiple variations of integration. Issue 1 (30th April 2019) - van Roekel, Henk-Jan; van der Steen, Martijn
Abstract : Purpose: This paper aims to uncover how implementation practices affect the unfolding of integration as the ideal of an enterprise resource planning (ERP) system. In this way, the authors aim to provide a better understanding of the ways in which the ideal of integration affects the complexity of ERP systems. Design/methodology/approach: This paper interprets a case study of the implementation of an ERP system in a Dutch company. Findings: The paper highlights how different variations of an object of integration were enacted during an ERP implementation. The authors observe how the interests of the various actors were not always served by the variations of integration in circulation. They illustrate how this resulted in a failure of the network to be folded into a taken-for-granted configuration of constituent parts. Consequentially, having multiple variations of integration contributed to increased complexity of the system. Originality/value: The paper highlights how multiple variations of a single object of integration are brought into circulation. Such perspective enables a better understanding of some of the complexities associated with ERP implementations.